The Influence of Islamic Work Ethic, Work Motivation, and Work Experience on Employee Quality in Completing Tasks at BMT Ummat Sejahtera Abadi Jepara - Istianah, Nur; Sa’diyah, Mahmudatus (Universitas Islam Negeri Raden Intan, 2023)
This research investigates the influence of Islamic work ethic, work motivation, and work experience on employee performance at BMT Ummat Sejahtera Jepara. The research design employed is quantitative. Primary data were collected through questionnaires distributed to BMT employees, while secondary data were obtained from online books, research journals, documentation, and available files. The population consists of 60 employees, and the sampling technique used is probability sampling with a census data approach.Data analysis in this study utilized Multiple Linear Regression with the SPSS application. The results indicate that the Islamic work ethic variable significantly impacts employee performance, as evidenced by the obtained T-value of 3.614, which exceeds the critical T-value of 1.673. The significance level (sig) is 0.00, indicating a probability value less than 0.05. Therefore, it can be concluded that the Islamic work ethic variable positively influences employee performance.Similarly, the motivation to work variable shows a positive impact, with a T-value of 3.255 exceeding the critical T-value of 1.673. The significance level (sig) is 0.002, indicating a probability value less than 0.05. Hence, it can be inferred that work motivation positively affects employee performance.On the other hand, the work experience variable exhibits a T-value of 1.030, which is less than the critical T-value of 1.673. The significance level (sig) is 0.308, indicating a probability value greater than 0.05. Consequently, it can be concluded from the test results that work experience does not have a significant positive effect on employee performance.